AN AIR QUALITY MONITORING STRATEGY FOR A SHIPYARD REGION (TUZLA, ISTANBUL, TURKEY) BASED ON DISPERSION MODELLING AND ON-SITE AMBIENT MEASUREMENTS - Saral, Arslan; Demir, Selami; Birpinar, Mehmet Emin (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2012)
An air quality modeling study was conducted to assess adverse effects of shipbuilding, repairing and maintenance activities within Tuzla Shipyards Region (TSR) on the ambient air quality. Emission data for volatile organic compounds (VOCs) and particulate matter (PM) emissions were determined using AP-42 emission factors and raw materials usage data obtained by a survey with the shipyard owners. Modelling was conducted with the meteorological data from 2005 to 2009 and hourly maximums, monthly and yearly averages were estimated using ISC3 (Industrial Source Complex v3) and MCGP 2.0 Visual. The model results were used to determine possible measurement points for ambient VOC and PM measurements. Twelve points were selected for ambient VOC sampling and five points were selected for ambient PM sampling within and around the TSR. Measurements were conducted at the selected locations for a period of two months. The measurement results were, in turn, compared with the model-predicted ambient concentrations at those points and the accuracy of the model was tested. The modelling attempt was found to be capable of explaining the dispersion mechanisms within the model domain. The model proved itself as a useful tool to predict ambient pollutant concentrations for distinct meteorological conditions and emission data.
Keywords: Air Pollution; PM10; VOC; Modelling; Measurement; Shipyard; AREA; Environmental Sciences & Ecology